FOSTERING ACTIVE LEARNING AND COLLABORATION IN ENGLISH CLASS THROUGH RALLY TABLE STRATEGY - Rahma Darini (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to examine the effectiveness of the Rally Table strategy in improving students’ English writing skills at the junior high school level. The research employed a quasi-experimental design with a pre-test and post-test non-equivalent control group design. The participants consisted of eighth-grade students from MTsS Al-Qosimiyah Sorek Satu, divided into experimental and control groups. The experimental group received writing instruction using the Rally Table strategy, a cooperative learning technique where students take turns contributing to a written task collaboratively. In contrast, the control group received conventional teaching methods. Data were collected through writing tests and analyzed using statistical methods to determine the significance of the improvement. The results indicated that students in the experimental group showed a significantly higher improvement in writing performance compared to those in the control group. These findings suggest that the Rally Table strategy can effectively enhance students’ ability to generate ideas, organize content, and use grammar and vocabulary appropriately in writing. It is recommended that English teachers integrate cooperative learning strategies such as Rally Table into their writing instruction to foster active participation and improve writing outcomes.